Kualitas Organoleptik Dangke dengan Penambahan Kayu Secang (Caesalpinia sappan L) pada Level yang Berbeda: Organoleptic Quality of Dangke with the Addition of Different Levels of Secang Wood (Caesalpinia sappan L) - Naheriastuti; Rajmi Faridah; Andi Kurnia Armayanti; Tri Astuti (Anoa: Journal of Animal Husbandry, 2022)
This study aims to determine the physical and organoleptic qualities of dangke with the addition of sappan wood (Caesalpinia sappan L) at different levels. This study used a completely randomized design (CRD) consisting of 5 treatments and 4 replications. The treatment used was the addition of sappan wood with levels of 0%, 1%, 1.5%, 2% and 2.5%. Parameters observed was organoleptic properties. The results showed that the addition of sappan wood had a high significant effect on organoleptic color, percentage of curd and whey. The conclusion of the research is the addition of sappan wood (Caesalpinia sappan L) with different levels can be used to increase the organoleptic value, especially as a natural dangke dye